La puerta videoescénica. Análisis de la interacción del espacio escénico y audiovisual en tres obras híbridas - Dr. Gustavo MONTES RODRÍGUEZ (Fonseca, Journal of Communication, 2023)
The video-scenic play is constructed through two modes of representation, the dramatic and the narrative of audiovisual enunciation through the introduction of audiovisual media in the representation. The spatial category is decisive in the creation of meaning, since communication with the viewer occurs in space. A projection screen, located on the stage, establishes the intermodal interaction between the scenic space and the audiovisual space.